2018
DOI: 10.1039/c8tb01672k
|View full text |Cite
|
Sign up to set email alerts
|

A resilient and flexible chitosan/silk cryogel incorporated Ag/Sr co-doped nanoscale hydroxyapatite for osteoinductivity and antibacterial properties

Abstract: A resilient and flexible chitosan/silk cryogel incorporated Ag and Sr co-doped hydroxyapatite exhibits good mechanical, antibacterial and osteoinductive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…With respect to the above features, SF porous scaffolds with high porosity, suitable mechanical properties, and biodegradability facilitate cell adhesion, proliferation, and migration as well as transmission of nutrients and wastes. , Although progress has been made recently in improving the pore structure and mechanical properties of these scaffolds, novel methods of generating pores, especially nanoscale pores, without sacrificing mechanical properties are still desired. Freeze-drying is a commonly used method for preparing SF porous scaffolds , where pore size, microstructure, and porosity can be modulated by controlling the freezing temperature, , cooling rate, and concentration of the SF solution used in the process. , Post-treatments including rinsing with methanol and water vapor annealing are needed to make the freeze-dried sponges water-insoluble. Methanol is the lowest-molecular weight alcohol and can rapidly permeate the protein structure to induce the transformation of SF from a random coil to a thermodynamically stable β-sheet structure, resulting in water insolubility of the SF scaffolds. However, methanol-treated scaffolds are relatively stiff and brittle and lack a high elastic modulus, which is critical in many areas of application for these scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the above features, SF porous scaffolds with high porosity, suitable mechanical properties, and biodegradability facilitate cell adhesion, proliferation, and migration as well as transmission of nutrients and wastes. , Although progress has been made recently in improving the pore structure and mechanical properties of these scaffolds, novel methods of generating pores, especially nanoscale pores, without sacrificing mechanical properties are still desired. Freeze-drying is a commonly used method for preparing SF porous scaffolds , where pore size, microstructure, and porosity can be modulated by controlling the freezing temperature, , cooling rate, and concentration of the SF solution used in the process. , Post-treatments including rinsing with methanol and water vapor annealing are needed to make the freeze-dried sponges water-insoluble. Methanol is the lowest-molecular weight alcohol and can rapidly permeate the protein structure to induce the transformation of SF from a random coil to a thermodynamically stable β-sheet structure, resulting in water insolubility of the SF scaffolds. However, methanol-treated scaffolds are relatively stiff and brittle and lack a high elastic modulus, which is critical in many areas of application for these scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Given the global threat and increasing influence of antibiotic resistance, there is an urgent demand to explore novel antibacterial strategies other than using antibiotics [[12], [13], [14], [15], [16], [17], [18], [19], [20]]. Recently, using a certain surface topography to provide a more persistent antibacterial solution attracts more and more attention [5,[21], [22], [23], [24], [25], [26]].…”
Section: Introductionmentioning
confidence: 99%
“…Figure demonstrates the live/dead ratio , for Gram-positive [Figure a] and Gram-negative [Figure b] bacterial cells on unpolarized and polarized BG, BG–10 NKN, BG–20 NKN, and BG–30 NKN samples. It has been observed that the live/dead ratio for both types of bacterial cells decreases with addition of the piezo­electric NKN as the secondary phase in BG [Figure ].…”
Section: Results and Discussionmentioning
confidence: 99%